h=1
2006-12-04 09:43:06
·
answer #1
·
answered by revasree 2
·
0⤊
0⤋
h=1
2006-12-04 17:26:20
·
answer #2
·
answered by ttjakt 6
·
0⤊
0⤋
3h - 5 = 2(4h - 5)
3h - 5 = 8h - 10 (Subtract 3h from both sides and add 10 to both sides)
5 = 5h (Divide both sides by 5)
h = 1
Check:
3(1) - 5 = 2(4(1) - 5)
3 - 5 = 2(4 - 5)
-2 = 2(-1)
-2 = -2
QED
2006-12-04 17:56:34
·
answer #3
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
3h-5=2(4h-5) distribute 2
3h-5=8h-10 subtract 3h from each side
-5=5h-10 add 10 to each side
5=5h divide by 5
h=1
2006-12-04 16:55:15
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
3h-5=2(4h-5)
3h - 8h = -10 + 5
-5h = -5
h = 1
Solution: h = 1.
<>><
2006-12-04 16:54:41
·
answer #5
·
answered by aeiou 7
·
0⤊
0⤋
3h - 5 = 8h-10
3h -8h = -10 + 5
-5h = -5
h = 1
2006-12-04 16:56:07
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
3h-5=2(4h-5)
3h-5=8h-10
-5=11h-10
5=11h
5/11=h
2006-12-04 16:54:49
·
answer #7
·
answered by qwerty 4
·
0⤊
1⤋
3h-8h=-10+5
-5h=-5
h=1
2006-12-04 16:53:28
·
answer #8
·
answered by Dupinder jeet kaur k 2
·
0⤊
0⤋